Liquid Crystal Modified Polylactic Acid Improves Cytocompatibility and M2 Polarization of Macrophages to Promote Osteogenesis - Zheng, Zexiang; Wang, Renqin; Lin, Jianjun; Tian, Jinhuan; Zhou, Changren; Li, Na; Li, Lihua (Frontiers in Bioengineering and Biotechnology, 2022)
Liquid crystalline phases (LC phases) are widely present in an organism. The well-aligned domain and liquidity of the LC phases are necessary for various biological functions. How to stabilize the floating LC phases and maintain their superior biology is still under study. In addition, it is unclear whether the exogenous LC state can regulate the immune process and improve osteogenesis. In this work, a series of composite films (PLLA/LC) were prepared using cholesteryl oleyl carbonate (COC), cholesteryl pelargonate (CP), and polylactic acid (PLLA) via a controlled facile one-pot approach. The results showed that the thermo-responsive PLLA/LC films exhibited stable LC phases at human body temperature and the cytocompatibility of the composites was improved significantly after modification by the LC. In addition, the M2 polarization of macrophages (RAW264.7) was enhanced in PLLA/LC films, and the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) was improved as co-cultured with macrophages. The in vivo bone regeneration of the materials was verified by calvarial repair, in which the amount of new bone in the PLLA-30% LC group was greater than that in the PLLA group. This work revealed that the liquid crystal-modified PLLA could promote osteogenesis through immunomodulation.